Contribution of Concept Mapping on the Improvement of Students’ Reading Comprehension of Open University of Bengkulu - Yusrizal Yusrizal (Universitas Negeri Padang, 2014)
In a distance learning program, UT is not only required to provide assistances in formulating independent learning materials, examination material, tutorials, practice classes, and examinations with the distance characters, but also to build students’ awareness to learn independently. Almost all learning resources at UT are in printed materials-books. Students must be prepared to learn independently to succeed in a distance learning program, supported by having a suitable strategy on reading of givens learning sources. The reading activities for students to exercise are very important in their independent learning. Therefore, comprehensing texts is crucial for academic success. The strategy is needed efficiently to increase students reading activity and practically enable students to understand a text comprehensively.Concept mapping is considered as one of strategies which hopefully used to improve student’s reading comprehension, especially for Open University student, whose a particular long distance characters of academic study. This strategy is provided since they can use their time effectively so that they can study regularly according to their own schedule. From the study of improving students’ reading comprehension by using concept mapping at sixth semester of PGSD program of Open University of Bengkulu, it was found that Concept Mapping can improve students’ reading comprehension. This can be evidenced from the students’ means which gradually improved in cycle one, two and three. In particular, the study provided the discussion of 7 indicators of reading comprehension that were improved by using concept maps during the research, as the result of Concept Mapping contribution.